Photodynamic Therapy 2021 - Mordon, Serge (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Photodynamic therapy (PDT) is a light-based photochemistry process. The illumination of a photoactivatable molecule (also called photosensitizer) with visible or near infrared light produces reactive oxygen toxic species to destroy tumor cells. This treatment modality leads to highly targeted actions, because reactive oxygen species are produced only where light is applied. Light is not harmful, nor is the photoactivable molecule. Only the combination of three elements (photosensitizer, oxygen, and light) is required to induce photo-oxidation reactions. PDT has proven to be a promising modality in many medical applications including cutaneous condition, infectious diseases, and various cancers at different stages. This book is a reprint of the Special Issue "Photodynamic Therapy 2021" that was published in Pharmaceuticals.